FIGURATIVE LANGUAGE IN THE SCARLET LETTER - Lilik Fadlilah (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2017)
The purpose of this witing is to give a brief understandable of figurative language used in the Scarlet Letter novel and add references to undertand the social value and its implication. Figurative language that stated in the novel connects any object or character to a symbolic meaning through simile, metaphor, allusion, or personification. Hawthorne’s main device for communicating his message in The Scarlet Letter is figurative language that make  the story flew strongly and has a highly stylized symbolic fable.The tight structure and figurative language of the novel  is like walking in to many-sided of mirrors where we see every fact in unending succession of relation to every other fact. In other side, this writing can be used to   broader knowledge about stylistics that it is reliable or recommended strategy in teaching linguistics and literature.